Faktor yang Mempengaruhi Prestasi Belajar Peserta Didik - Yuzarion Yuzarion (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2017)
Abstract: The results showed that the structural model has a decent (GFI = 0.930, AGFI = 0.908 > 0.90; CFI = 0.990, TLI = 0.988 > 0.95, and RMSEA = 0.029 < 0.08) and obtain the support of empirical data (X2 = 169.029 and p = 0.068 > 0.05). Factors parents attitudes toward children, the attitude of teachers toward students, and self-regulated learning influence on student achievement. Parents’ attitudes toward children, the attitude of teachers towards students direct effect on self-regulated learning and indirect effect on student achievement through self-regulated learning. These findings support the social cognitive theory.Abstrak: Hasil penelitian menujukkan bahwa model struktural layak (GFI = 0,930, AGFI = 0,908 > 0,90; CFI = 0,990, TLI = 0,988 > 0,95; dan RMSEA = 0,029 < 0,08) dan memperoleh dukungan data empiris (X2 = 169,029 dan p = 0,068 > 0,05). Faktor sikap orangtua terhadap anak, sikap guru terhadap peserta didik, dan self-regulated learning berpengaruh terhadap prestasi belajar peserta didik. Sikap orangtua terhadap anak, sikap guru terhadap peserta didik, berpengaruh langsung terhadap self-regulated learning dan berpengaruh tidak langsung terhadap prestasi belajar peserta didik melalui self-regulated learning. Temuan ini mendukung teori kognitif sosial.